Trends Analysis of Contraceptive Use and Teenage Pregnancy Amongst Adolescents in Ghana Using the Demographic and Health Survey 1998, 2003, 2008 And 2014 - Kadiri - English, A. (University of Ghana, 2020)
Background: Teenage Pregnancy and Contraceptive use are issues of concern both nationally and internationally. They are also integral aspects of achieving sustainable development by 2030. Despite interventions to reduce teenage pregnancy and increase contraceptive use, there are still high and increasing teenage pregnancy rates alongside low contraceptive use. General objective: To analyse the trend and factors associated with contraceptive use and teenage pregnancy in Ghana using the 1998 to 2014 Demographic and Health Surveys (DHS). Methodology: A cross-sectional study using secondary data from the Ghana Demographic and Health Surveys (GDHS) of 1998, 2003, 2008, and 2014. The GDHS employed a stratified two-staged cluster sampling method. Only quantitative data was used. Data were analysed using Microsoft Excel 2019 and Statistical Package for the Social Sciences (SPSS) version 20. Pearson Chi-Square was used to determine the association between teenage pregnancy or the use of a contraceptive method (dependent variables) against independent variables which were age, educational level, religion, place of residence, region, age at first sex, marital status, ever given birth, and heard family planning on radio/TV/newspaper. Statistically significant variables were further analysed using a binary logistic regression and an adjusted odds ratio (AOR) at 95% confidence interval (CI) was calculated to determine the strength of the association. The first and second binary logistic regression model was fitted with the data with contraception use and teenage pregnancy respectively being the response variables and predictors being age, region, religion, place of residence, educational level, age at first sex, year of survey, and heard family planning on radio/TV/newspaper. Permission was sought from the DHS program for access and use of the datasets for the analysis. Sample weights were applied to obtain representative data at the national level. Results: After applying sample weights, there was a total of 910, 1148, 1025, and 1625 respondents for 1998, 2003, 2008, and 2014 surveys respectively. The mean age of the respondents was 17 and a standard deviation of 1.4. The adolescent girls had high knowledge of contraceptives starting from 86.9% in 1998 to 96% in 2014. There was only a 0.1% increase in contraceptive use over the survey years (8.6% in 1998 and 8.7% in 2014) and a 1.5% increase in modern contraceptive use (4.8% in 1998 and 6.3% in 2014). The use of any contraceptive method had a decreasing pattern from 1998 to 2008 and increased in 2014. The use of a modern contraceptive method however had a fluctuating pattern over the survey years. The condom was the modern contraceptive method of choice among the adolescents in all the surveys. Whiles the use of oral contraceptive pills had a decreasing pattern, the use of IUD and injectables had an increasing trend. Radio was the commonest source of information on contraceptives followed by television then newspaper. Age and age at first sex were significantly associated with contraceptive use in all four surveys (p <0.001). Source of information from television and being a teenage mother were significantly associated with contraceptive use in three of the surveys whiles religion, educational level, region, and source of information from radio and marital status were significant in two surveys (p < 0.05). Teenage pregnancy was also significantly associated with modern contraceptive use in all four surveys (p = 0.000). For the logistic regression, region, educational attainment, and source of information from the newspaper were determinants of contraceptive use (p < 0.05). Those with no education were 45% less likely to use contraceptives as compared to those with at least secondary level education. There was a 0.6% increase in teenage pregnancy over the survey years with the odds of teenage pregnancy decreasing over the years. There was an increase in TP from 2003 to 2014 whiles there was a reduction from 1998 to 2003. Age, educational level, rural/urban residence, and age at first sex were significantly associated with teenage pregnancy in all four surveys (p < 0.05). For the logistic regression, age, age at first sex, region and educational level were determinants of teenage pregnancy (p < 0.05) Those who had their first sex from 15-17 years and below 15years were 84% and 37% respectively less likely to be pregnant as teens as compared to those who had their first sex from 18-19 years. For the highest educational level, those who had no education and those with only primary education were each 2.3 times more likely to be pregnant as teens as compared to those with secondary education. Conclusion: There was low contraceptive use despite high knowledge throughout the survey years. This study suggests that keeping girls in school at least to the secondary level, improving access to and use of modern contraceptive methods, as well as provision of sexual and reproductive health information on radio, television, and newspaper can support the fight in addressing high teenage pregnancy rates and low contraceptive use.
MA. Public Health
Keywords: Teenage pregnancy; Contraceptive use; Reproductive health; Ghana